Realización de un cortometraje animado sobre el turismo como problemática ambiental en el Parque Nacional Galápagos - Pazmiño Carrera, Daniel Alberto (2020)
The Galápagos National Park has been benefited but also prejudiced by tourism throughout history. The lack of education in what responsible tourism is about, has played an important part in the contamination and environmental problems that exist within the Enchanted Islands. On the other hand, animation inside of Ecuador has grown in an exponential way in the last few years. Every day there are new animated projects, and with this there has been an increment in the given support not only by the governmental institutions, but also in the audience itself. To tell a story with an audiovisual animated product with the purpose of educating the spectator can be one of the most efficient ways to communicate the message or idea that someone has, this is the reason why this process has been chosen for this product.